An Endeavor of Freedom: Modern Anthologies of Ukrainian Free Verse - Naumenko, Nataliia (My University, 2018)
The main problem of researching the semantics of free verse and its translations is that every literary critic is free to look at this intricate genre, choosing one’s own set of tropes and figures to interpret it in written form. These facts were considered in this study of original Ukrainian free verse works and their interpretations, regarding the specific treats of languages to use. The anthology Вільний вітер. Волен вятър published in Kharkiv in 2017 became a material for this research. This issue makes a good opportunity for one reader to get acquainted with Bulgarian culture, and for another to actualize their knowledge about this country on Black Sea coast. The 20th century free verse writing represents quite active and flexible use of natural philosophical imagery in the artistic texture of the poems. These are different functions for it to fulfill (from decorating the lyrical narration up to expression of an essence of the work), stylistic means, and formation of the new connotations on the base of traditional meanings. Studying the interpretations of traditional genres and their poetics in compositional and lingual dimensions of both Ukrainian and Bulgarian free verses (those included into Вільний вітер) allowed seeing the fact: the more the author gets into the internal world of the character and one’s relationships with nature, the wider becomes the circle of meanings for the cultural conceit, image, and symbol. Furthermore, the larger research field gets opened for comparison of aforesaid meanings in various languages, not only Ukrainian and Bulgarian.
Keywords: poetry; free verse; translation; genre; style; language; поезія; вільний вірш; переклад; жанр; стиль; мова; кафедра іноземних мов професійного спрямування